Pituitary-adrenal activity and opioid release in ponies during thiopentone/halothane anaesthesia - Luna, Stélio Pacca Loureiro [UNESP]; Taylor, P. M. (Elsevier, 1995)
The effect of thiopentone/halothane anaesthesia on the release of endogenous opioid, adrenocorticotrophin, arginine vasopressin, cortisol and catecholamine was investigated in ponies. The contribution made by halothane itself was studied by maintaining six ponies with a constant 12 per cent end tidal halothane concentration and five with a concentration ranging between 0.8 and 12 per cent. Cardiorespiratory depression was more prolonged in the ponies receiving a constant 1-2 per cent end tidal halothane concentration than in those which received less halothane. Plasma lactate concentration increased and haematocrit decreased during halothane anaesthesia. The concentrations of met-enkephalin, dynorphin and catecholamines did not change and those of β-endorphin, adrenocorticotrophin, arginine vasopressin and cortisol increased during halothane anaesthesia. Halothane appeared to be a major stimulus to pituitary adrenocortical activation because the adrenocortical secretion was proportional to the amount of halothane inhaled. β-endorphin increased proportionally more than adrenocorticotrophin and their plasma concentrations were not correlated, suggesting that they have independent secretion mechanisms.
Keywords: anesthetic agent; argipressin; beta endorphin; catecholamine; corticotropin; dynorphin; endorphin; halothane; hydrocortisone; metenkephalin; thiopental; anesthesia; animal experiment; concentration response; controlled study; hormone release; hypophysis adrenal system; inhalational drug administration; male; nonhuman; respiration depression; Analysis of Variance; Anesthesia, General; Anesthetics, General; Animal; Dose-Response Relationship, Drug; Halothane; Hemodynamics; Horses; Male; Opioid Peptides; Pituitary-Adrenal System; Respiration; Support, Non-U.S. Gov't; Thiopental; Animalia